Legal Protection for Trademark Applicatints in Good Faith in Retroactive issuance of Certificate Based On Supreme Court Decision - Pramana, Muhammad Aditya; Fuad, Fokky; Suartini, Suartini (DiH: Jurnal Ilmu Hukum, 2025)
The process by which a trademark certificate issued by the Directorate General of Intellectual Property is retroactively valid from the date the trademark registration application is submitted, not from the date the certificate is officially issued . brand which was resolved through criminal channels in Court Nganjuk State with the Defendant Rudy Mulyanto who can analyzed more far is a dispute between Trademarks resolved through criminal channels which then in the Cassation Decision at the Supreme Court Number 3733 K / Pid.Sus / 2020 Rudy Mulyanto was declared not legally and convincingly proven guilty of committing a crime as in the First or Second indictment. The research method used is normative juridical library materials or secondary data as basic material for research by conducting a search for regulations and literature related to the problem being studied. The results of this study are that legal protection for trademark certificates issued by the Directorate General of Intellectual Property of the Ministry of Law and Human Rights of the Republic of Indonesia is retroactive from the date of submission of the application, not from when the certificate was issued. In the Decision of this trademark dispute case, there was negligence in providing legal protection to the applicant or trademark registrant, the author does not agree with the decision of the panel of judges at the first level and the high court level and concludes that trademark disputes should be resolved first through civil channels, while criminal channels are used as a last resort in resolving trademark disputes.